Reimagining Fiscal Policy in Indonesia: Integrating Islamic Fiscal Instruments for Equitable and Sustainable Public Finance - kartika marella vanni; Agus Sulistiyono (Institut Agama Islam Negeri Lhokseumawe, 2026)
This study examines the implementation of fiscal policy in Indonesia from the perspective of Islamic economics. The discussion is motivated by the persistent structural pressure on the state budget: the 2024 budget closed with a deficit of IDR 507.8 trillion, equivalent to 2.29 percent of gross domestic product, while the tax ratio fell to 10.08 percent, the lowest among comparable economies in the region, and outstanding central government debt reached IDR 9,637.9 trillion by the end of 2025. At the same time, the redistributive capacity of the existing fiscal system remains limited, as indicated by a Gini ratio of 0.375 in March 2025, and the national zakat potential of IDR 327 trillion is largely untapped, with actual collection of only around IDR 41 trillion. This research applies a qualitative approach using library research, drawing on academic books, scholarly articles, statutory documents, and official government publications, which are then examined through content analysis. The findings show that fiscal policy in Islamic economics rests on the principles of justice, efficiency, and public benefit, as demonstrated during the era of the Prophet Muhammad and the Rightly Guided Caliphs, when expenditure was calibrated to actual revenue and administered through the baitul mal. In Indonesia, several Islamic fiscal instruments have been partially absorbed into the national system, most notably zakat as a deduction from taxable income, yet regulatory ambiguity and weak inter-institutional coordination persist. The study recommends strengthening the synergy between zakat and taxation and formulating fiscal policy grounded in Islamic values more systematically.